Cultural heritage as a driver for human development: an assessment of the socio-cultural benefits at Matendera ruins Buhera - Kuzonyei, Naboth Trust (Midlands State University, 2017)
This research study focused on heritage as a driver for human development and makes an assessment of the socio-cultural benefits of heritage tourism use to communities surrounding heritage places. The thrust of the study was to know how Matendera ruins as a heritage resource has benefited the surrounding communities socio-culturally. The study reveals the extent of the Collett plan in enabling community development from heritage tourism, the of community involvement at Matendera and how communities surrounding Matendera have benefited to develop indirectly from the use of Matendera as a tourist attraction. The researcher made use of the case study approach to collect data. The study revealed that communities surrounding Matendera were benefiting from the heritage tourism culturally, educationally, socially, psychologically and environmentally. Community members have pride and they enjoy the benefits they get from Matendera for example the Matendera festival and the kudyarima environmental project. The Matendera festival also boosts the socio-cultural benefits. It also benefits their livelihood, social harmony and inclusion. The study also shows that the developmental strategy by Collett guided the tourism use of Matendera. The research findings showed that the Collett plan was applicable to Matendera and communities surrounding Matendera but nothing is mentioned about communities benefiting. The Collett plan is being implicated at Matendera but the implications are limited. There is need develop policy for community beneficiation like the nation heritage and tourism strategy of South Africa and also the revision of Collets plan and come up with a new plan for communities surrounding Matendera to benefit more socio-culturally.